Pengaruh aplikasi pasta buah aren (Arenga pinnata) terhadap mortalitas hama keong emas (Pomacea canaliculata L.) di rumah kaca - Wibowo, Lestari; Pratiwi, Irene Indah; Efri, Efri; Solikhin, Solikhin (Universitas Lampung, 2025)
Many studies have shown that botanical pesticides are safe for controlling pest problems in the field. Arenga fruit paste has been suggested to contain secondary metabolites that can help manage golden apple snail infestation. The objective of this research was to determine the effect of arenga fruit paste application on the feeding activity and mortality of golden apple snails. This study used a completely randomized design with different treatment concentrations of arenga fruit paste, namely 0, 1, 2, 4, 6 g per L of living medium, with four replications. The results showed that the application of arenga fruit paste decreased feeding activity and increased mortality of golden apple snails. At the highest concentration, 6 g per L of live medium, food consumption was reduced to only 10%, resulting in the highest mortality rate of 80%.